2014
DOI: 10.1002/ppul.22989
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy and safety of aerosolized tobramycin 300 mg/4 ml in cystic fibrosis

Abstract: Overall, TNS4 demonstrated short-term clinical benefits similar to TNS5 which were maintained during the long-term use of TNS4 and was also associated with a favorable tolerability profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 30 publications
(87 reference statements)
0
22
0
Order By: Relevance
“…A comparison of in vitro aerosol performance and in vivo pharmacokinetics of Bramitob® vs TOBI® demonstrated no significant difference between the formulations, with the exception of slightly higher drug levels in sputum at 30 mins postinhalation, a likely consequence of the 25% higher drug concentration within the formulation [60]. Recently, an extensive two-phase study comparing the long term (56 weeks) efficacy and safety of Bramitob® and TOBI® again concluded that clinical outcomes were comparable between the two formulations [37]. Both formulations have been demonstrated to be comparable in terms of their in vitro antimicrobial efficacy against clinical PA CF isolates [61].…”
Section: Formulation Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of in vitro aerosol performance and in vivo pharmacokinetics of Bramitob® vs TOBI® demonstrated no significant difference between the formulations, with the exception of slightly higher drug levels in sputum at 30 mins postinhalation, a likely consequence of the 25% higher drug concentration within the formulation [60]. Recently, an extensive two-phase study comparing the long term (56 weeks) efficacy and safety of Bramitob® and TOBI® again concluded that clinical outcomes were comparable between the two formulations [37]. Both formulations have been demonstrated to be comparable in terms of their in vitro antimicrobial efficacy against clinical PA CF isolates [61].…”
Section: Formulation Developmentmentioning
confidence: 99%
“…Tobramycin solution for inhalation has been demonstrated to be effective -however, administration times for nebulised tobramycin can be lengthy (~15 -22 mins [37]), which affects patient compliance with therapy. The time spent setting up nebulisers, cleaning equipment and administering the therapy contributes to even longer times in total for nebulised therapy (~41 mins per day for adult CF patients [62]).…”
Section: Formulation Of Tobramycin -Development Of Dry Powder Formulamentioning
confidence: 99%
“…Concentrated solutions of tobramycin for inhalation (75 mg/ml formulated in 4 ml) enable delivery of a more highly concentrated solution with the same total dose of tobramycin compared with TIS (300 mg/5 ml of tobramycin). This allows for delivery in a somewhat shorter period of time (approximately 15 min), achieving a higher peak sputum concentration compared with TIS [43]. Concentrated tobramycin solution for inhalation is currently marketed in multiple countries (Bramitob ® ; Chiesi Farmaceutici, Parma, Italy [44] and Bethkis ® ; Chiesi USA, Inc., NC, USA [45]).…”
Section: Concentrated Tobramycin Solutions For Inhalationmentioning
confidence: 99%
“…Tobramycin solution for inhalation (TSI) (300 mg/5 ml for 28 days) was found to be equally effective for eradication of PA compared to tobramycin (80 mg/2 ml twice daily for 365 days) . Use of a more concentrated form of tobramycin led to no differences in FEV1% predicted, increased bacterial load, or side effects, and no change in the safety profile . A new solution (T100) administered via eFlow™ showed a higher area under the curve (AUC) and maximum concentration (C max ) in sputum and lower AUC and C max in serum .…”
Section: Diagnosismentioning
confidence: 99%